Falhas no processo simbólico e tradutivo : um olhar da psicossomática contemporânea - Deitos, Eliane Tomasi (My University, 2025)
A field of countless enigmas, the body has been investigated by psychoanalysis as a representative of a stage of psychic disorders in the metapsychological understanding, bringing to light the investigations of the somato/psychic borders in the subject. The present study deals with the professional master dissertation project in Psychology at the University of Caxias do Sul, emphasizing contemporary manifestations and what is presented at the basis of these phenomena based on Freudian and post-Freudian psychoanalytic theory. Following this purpose, perceptions of the body are addressed from Freud, studies on hysterical symptoms, moving on to more serious pathologies in contemporary times. This research does not deny the biological factors involved in psychosomatics, but has the intention of discussing the topic, from an ethical and epistemological position of psychic/physical suffering. The study relies mainly on the discussion of the contributions of Jean Laplanche, in his theory of Generalized Seduction, regarding the symbolic and translational capabilities or failures of what was marked in the I-body in times of autoerotism. This work includes research conducted at a dermatology clinic with three patients who have skin conditions and who participated in individual interviews. This illustration provides a rich and in-depth discussion of the cases. It can be seen from this research that these patients who have skin conditions carry within themselves something that they were unable to metabolize from their childhood and that erupted in the body during adolescence, a time of narcissistic, Oedipal and hormonal potentialities, bringing to the surface something of the subjectivity that they were no longer able to digest or integrate. These conditions take on a more violent character in adulthood when a greater conflict approaches, such as separations or difficulties in tolerating a more adult life. What cannot be processed psychologically ends up being discharged in the body. [resumo fornecido pelo autor]
Campo de inúmeros enigmas, o corpo tem sido investigado pela psicanálise como representante de um palco de distúrbios psíquicos no entendimento metapsicológico, trazendo à tona as investigações das bordas somato/psíquicas no sujeito. O presente estudo trata do projeto de dissertação de mestrado profissional em Psicologia da Universidade de Caxias do Sul, enfatizando as manifestações contemporâneas e o que se apresenta na base destes fenômenos a partir da teoria psicanalítica freudiana e pós-freudiana. Seguindo este propósito, aborda-se percepções do corpo desde os estudos de Freud acerca dos sintomas histéricos, seguindo para patologias mais graves na contemporaneidade. Esta pesquisa não nega os fatores biológicos envolvidos na psicossomática, mas tem a intenção de discutir a temática, numa posição ética e epistemológica do sofrimento psíquico/físico. O estudo conta, principalmente, com a discussão das contribuições de Jean Laplanche, em sua teoria da Sedução Generalizada, a respeito das capacidades ou fracassos simbólicos e tradutivos daquilo que ficou marcado no Eu-corpo em tempos de autoerotismo. Este trabalho contempla uma pesquisa realizada junto a uma clínica dermatológica, com três pacientes que apresentam afecções na pele e que participaram de entrevistas individuais. A partir desta ilustração, desenvolve-se uma discussão rica e profunda dos casos. Pode-se identificar, diante desta pesquisa, que tais pacientes que apresentam afecções na pele carregam dentro de si algo que não conseguiram metabolizar da sua vida infantil e que, eclodiu no corpo pela época da adolescência, momento de potencialidades narcísicas, edípicas e hormonais, trazendo a tona algo da subjetividade que já não conseguiam digerir, integrar. Tais afecções tomam um caráter mais violento na adultez quando um conflito maior se aproxima como as separações, as dificuldades em tolerar uma vida mais adulta, o que não pode tramitar psiquicamente acaba por ser descarregado no corpo. [resumo fornecido pelo autor]
Keywords: Medicina psicossomática; Psicologia; Psicanálise; Medicine, Psychosomatic; Psychology; Psychoanalysis